2019
DOI: 10.1136/bmjopen-2018-026904
|View full text |Cite|
|
Sign up to set email alerts
|

Acupuncture for chronic neck pain with sensitive points: study protocol for a multicentre randomised controlled trial

Abstract: IntroductionChronic neck pain is a challenging condition to treat in clinical practice and has a considerable impact on quality of life and disability. According to the theory of traditional Chinese medicine, acupoints and tender points may become sensitised when the body is in a diseased state. Stimulation of such sensitive points may lead to disease improvement and improved clinical efficacy. This study aims to evaluate the efficacy and safety of needling at sensitive acupoints in providing pain relief, impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The SF-MPQ, also, includes the Present Pain Intensity (PPI) index with 1 item and 1 item for a 10 cm visual analogue scale (VAS) for average pain. SF-MPQ has acceptable psychometric properties and it has been used in several studies of chronic pain, like athletes’ knee, 25 neck pain, 26 etc. The SF-MPQ has been translated into many languages, including Arabic, 27 Brazil, 28 Greek, 29 etc.…”
Section: Methodsmentioning
confidence: 99%
“…The SF-MPQ, also, includes the Present Pain Intensity (PPI) index with 1 item and 1 item for a 10 cm visual analogue scale (VAS) for average pain. SF-MPQ has acceptable psychometric properties and it has been used in several studies of chronic pain, like athletes’ knee, 25 neck pain, 26 etc. The SF-MPQ has been translated into many languages, including Arabic, 27 Brazil, 28 Greek, 29 etc.…”
Section: Methodsmentioning
confidence: 99%
“…61 Other clinical trials have been proposed or are currently being pursued for acupuncture and its efficacy in narrower clinical contexts such as cervical spondylosis, osteoporosis, spinal cord injury, or more specific control parameters. [47][48][49]51,56 A 2018 trial using electromyography and subjective pain outcomes found no significant difference between traditional and sham acupuncture. 37 Similar results were found in a 2020 trial using video-guided acupuncture, which were compared with results from a previous study on sham acupuncture, finding no difference in outcomes between modalities.…”
Section: Acupuncture For Chronic Musculoskeletal Painmentioning
confidence: 99%
“…The study’s design is to randomize 175 recruited patients into five separate groups: a traditional acupuncture group (group A), a shallow-puncture group (group B), a non-acupoint acupuncture group (group C), a non-acupoint shallow-puncture group (group D), and a sham-puncture group (group E) ( 87 ). Other planned trials will evaluate acupuncture for spondylosis ( 88 ), compare high and low sensitivity acupuncture to sham ( 89 ), and collect biometric data comparing healthy volunteers and participants with NSNP ( 90 ).…”
Section: Acupuncture and Needling For Neck Painmentioning
confidence: 99%